Women Employee Work-life and Challenges to Industrial Relations: Evidence from North Kerala - S. Rajesh and Manoj P K
According to the International Labor Organization global employment trends report of 2013, the rate of women participation as India’s labor force has dropped from 37 percent in 2004-05 to 29 percent in 2009-10. Needless to say that woman in India faces enormous challenges when they participate in the fluctuations of the country’s economy. The challenges faced by women, whether the economy gets boosted or gets depressed is a reflection of the amount of injustice they suffer in the society at large, particularly at the middle class level or the grassroots level. There is always protective labor legislation, made compatible to the rising productivity and economic growth. Study reveals that a big proportion of female workers have struggled to achieve minimal standards at the work place level. This however should not prompt one to conclude that labor legislation is a means to protect the female workers from gender discrimination at workplace. Today’s social standards make it necessary for the women to work, support her family financially. This moves the women, especially the Indian women out of her home causing lot of imbalances in their work, family and personal ego. The nature of imbalances range from physical to psychological. This naturally tells upon her work efficiency as well as domestic management. Besides, in the Indian society working women faces lot of problems just by virtue of being a woman. The workplace atmosphere introduces a sedentary life style which aggravates things like anxiety, depression, faulty eating habits and lack of sleep. Awkward working hours, job related pressures, increase the problem of balancing home and office responsibility. Such problem desist a woman from staying in the job. The present article here aims to project problems of women employees in industrial sector of the northern regions of Kerala state and show how their predicament can pose challenges to the concept of cordial industrial relationship, so essential for the overall boosting of economic in the industrial sector.